Patent ductus arteriosus with persistent pulmonary artery hypertension after transcatheter closure - Feng, Jianqi (Ther Clin Risk Manag, 2016)
OBJECTIVES: To observe the change in pulmonary artery systolic pressure (PASP) of patients with persistent pulmonary arterial hypertension (PAH) after patent ductus arteriosus (PDA) occlusion. BACKGROUND: After occlusion of PDA in patients with PAH, some patients still tend to suffer from persistent PAH. METHODS: A chest X-ray, an electrocardiogram, and an echocardiogram were performed on nine patients at 24 hours, 1 and 6 months, and 1 year serially. RESULTS: There was a significant fall (P<0.05) in mean PASP after occlusion (to 59.3±12.7 mmHg). However, the aortic pressure and systemic arterial oxygen saturation changed slightly (P>0.05). During the follow up, there was a further fall in the PASP in five patients (No 1, 5, 6, 7, and 8). Four patients (No 2, 3, 4, and 8) showed the evidence of worsening PAH and were treated with sildenafil. Patient 2 died from acute right heart failure after a period of 11 months from the time of transcatheter closure, triggered by pulmonary infection. CONCLUSION: Some patients with borderline hemodynamic data with PDA and PAH can deteriorate or keep sustained PAH after PDA closure. The treatment of permanent closure to these patients must be cautious.